Model of The Effect of Facilities, Service Quality Through Passenger Trust on Customer Satisfaction at Terminal 3 Soekarno–Hatta Airport In 2025 - Dilalailaty Dilalailaty; Cecep Pahrudin; Yana Tatiana (Dinasti Review, 2026)
This study aims to analyze the effects of facilities and service quality on customer satisfaction, with customer trust as a mediating variable, at Terminal 3 of Soekarno–Hatta International Airport in 2025. A quantitative approach with a survey method was employed. Data were collected through questionnaires distributed to 280 passengers using Terminal 3. The data were analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The results show that facilities and service quality have a positive and significant effect on customer satisfaction and customer trust. Customer trust also has a positive and significant effect on customer satisfaction. Furthermore, customer trust significantly mediates the relationship between facilities, service quality, and customer satisfaction. These findings indicate that improving passenger satisfaction requires not only better facilities and service performance but also the ability of airport management to build and maintain passenger trust.